2021
DOI: 10.5435/jaaos-d-20-00974
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Side of the Injured Athlete

Abstract: The psychosocial benefits of participating in sports have long been appreciated. However, athletes are often faced with circumstances that make them susceptible to psychological challenges unique to the athletic population. One such circumstance is injury in sport, which can be a source of notable distress and may precipitate the emergence of new or exacerbation of underlying psychological disorders. In athletes who are injured, particularly those undergoing surgical intervention, psychological factors play a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 58 publications
0
52
0
Order By: Relevance
“…Psychological factors are a key component in recovery for the injured athlete, as studies have shown that individual personality traits, fear of reinjury, and loss of interest all affect the ability to successfully RTP. 2 , 5 , 13 In a recent systematic review, Nwachukwu et al 13 determined that psychological factors comprised 64.7% of the reasons that patients were unable to RTP after anterior cruciate ligament (ACL) reconstruction. Further, there exists evidence that psychological factors affect RTP after UCL reconstruction as well.…”
mentioning
confidence: 99%
“…Psychological factors are a key component in recovery for the injured athlete, as studies have shown that individual personality traits, fear of reinjury, and loss of interest all affect the ability to successfully RTP. 2 , 5 , 13 In a recent systematic review, Nwachukwu et al 13 determined that psychological factors comprised 64.7% of the reasons that patients were unable to RTP after anterior cruciate ligament (ACL) reconstruction. Further, there exists evidence that psychological factors affect RTP after UCL reconstruction as well.…”
mentioning
confidence: 99%
“…[22][23][24] With the prevalence of eating disorders growing and the rise in sport participation and specialization among pediatric and adolescent patients, increasing numbers of patients may be at risk of developing disordered eating habits. 1,2 Future research should investigate more directly and prospectively whether pediatric and adolescent patients experience disordered eating after sports or trauma surgery using a variety of metrics, such as patient and parent questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Following injury, female athletes are at increased risk of developing disordered eating habits, which has been attributed to the lifestyle changes associated with sports injuries. 1,2 Disordered eating commonly is defined as an abnormal eating behavior involving restrictive eating, fasting, skipping meals, using diet pills, laxatives, diuretics, enemas, or binge eating followed by purging (i.e., vomiting). 3,4 Many of these behaviors are formed in adolescence, enhancing the susceptibility of the young female athlete population to develop disordered eating.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological factors including self-efficacy, identity, and fear of reinjury may all play a role in an athlete's ability to return to sport. 48 Previous studies have reported that female athletes recovering from injury are often self-directed and exhibit greater levels of anxiety concerning an injury's impact on their lives and a loss of physical self-worth with injury when compared with their male counterparts. [49][50][51] Gennarelli et al 52 conducted a systematic review evaluating outcomes after psychosocial interventions to help facilitate recovery after musculoskeletal sports injuries and showed positive mood changes, improved pain management, and better exercise compliance and rehabilitation adherence when the following interventions were incorporated during rehabilitation: relaxation and/or guided imagery, positive self-talk, goal setting, counseling, emotional and/or written disclosure, and modeling videos.…”
Section: Psychological Considerations In Return To Sport In Female Athletesmentioning
confidence: 99%